The Politics of Benevolence: Political Patronage of Party-Based Charitable Organizations in Contemporary Indonesian Islam - Latief, Hilman (Al-Jamiah: Journal of Islamic Studies, 2013)
The rise of party-based Islamic charities has had a profound impact on the nature of philanthropic activities in contemporary Indonesia, and stimulated a new debate over the issue of the politics of benevolent acts. Over the past few years, in line with the increase of the influence of the Islamic factor in Indonesian politics, there have been a number of political parties which actively engaged with social welfare activities through the newly-established Islamic charitable organizations. The close ties between charitable organizations and political parties may lead to the new patterns of Muslim social and political activism, and to the new forms of political clientelism. This article analyzes the vibrant effort of political parties in sponsoring the inception and operation of Islamic charitable organizations in the post New Order era, and investigates how political clientelism has been established through charity practices. This paper compares the roles of charitable organizations set up by the nationalist and Islamist parties in formulating strategies to promote their political interest. Based on three political parties studied in this article, which are the Prosperous Justice Party (PKS), Golkar Party, and the Indonesian Democratic Party of Struggle (PDI-P), this paper argues that the practice of charity has become a popular way used by politicians to patronize their constituents, but at the same time, this practice has weakened the Muslim perspective of development and social change.[Munculnya lembaga-lembaga amal yang dikelola oleh partai politik berpengaruh luas terhadap aktifitas filantropi di Indonesia dan memicu perdebatan seputar politik-kedermawanan. Dalam beberapa tahun terakhir, selaras dengan semakin meningkatnya pengaruh Islam dalam lanskap politik Indonesia, partai-partai politik juga berlomba-lomba untuk terlibat aktif dalam aktifitas filantropi dengan mendirikan lembaga amal. Ikatan kuat antara partai politik dan lembaga amal tersebut tentu berpotensi melahirkan pola aktivisme sosial-politik Islam dan bentuk baru clientisme-politik. Artikel ini akan mengulas upaya keras partai politik dalam mendirikan dan mengendalikan lembaga-lembaga amal pasca Orde Baru dan menjelaskan bagaimana clientisme dapat terbentuk melalui aktifitas amal. Artikel ini akan membandingkan peran lembaga-lembaga amal yang didirikan oleh partai politik nasionalis dan Islam dalam menyusun strategi untuk menyukseskan agenda politik mereka. Dengan menganalisis tiga partai politik, Partai Keadilan Sejahtera/PKS, Partai Demokrasi Indonesia-Perjuangan/PDI-P, dan Golongan Karya/Golkar, penulis berargumen bahwa aktifitas amal semakin populer di kalangan politisi sebagai cara menarik simpati konstituen, tetapi pada saat yang sama, praktik tersebut semakin memperlemah cara pandang umat Islam mengenai pembangunan dan perubahan sosial.]